La cara oculta de la desamortización municipal española (1766-1856) - José-Ignacio Jiménez-Blanco; Antonio M. Linares Luján (Historia Agraria)
The existence of an intense process of municipal privatization in Spain prior to the General Disentailment Act of 1855 has still not entered fully into historiographical treatment of the liberal agrarian reform, despite contributions by specialized literature in recent decades. This article aims to reexamine the phenomenon based on the hypothesis that the privatizing discourse of Spanish liberalism was the result of a long process of transformation in the rural world. To this end, the article analyzes the complex and tortuous path of the three episodes that led to the processes of census redemption resulting from the Act of 1 May 1855: the division of land initiated during the reign of Charles III, census-based land distr ibution between the 1820s and 1840s, and illegal land cultivation since the Spanish War of Independence. Our goal is twofold: on the one hand we aim to define concepts that have not been fully understood and, secondly, to enrich the debate regarding the privatization process with a specific emphasis on proposals that within liberalism sought to use municipal rustic wealth to modify the str ucture of land ownership, with var ying degrees of success.